2016
DOI: 10.1097/rlu.0000000000001238
|View full text |Cite
|
Sign up to set email alerts
|

Occult Mediastinal Yolk Sac Tumor Producing α-Fetoprotein Detected by 18F-FDG PET/CT

Abstract: Malignant mediastinal yolk sac tumor (YST), especially adult onset, is rare. Herein, we report a case of occult mediastinal YST with α-fetoprotein production revealed by F-FDG PET/CT in a young adult, in which the intense tracer uptake was demonstrated in the anterior mediastinum. This case indicates F-FDG PET/CT may be a useful tool for detecting the occult primaries of YST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…1,2 The extragonadal YSTs are usually seen in anterior mediastinum, retroperitoneum, and suprasellar regions. [3][4][5][6] In this case, the YST was in the pineal gland, which is relatively rare. Moreover, we found that 68 Ga-FAPI PET showed a far better tumor-to-background ratio than 18 F-FDG in the intracranial YST.…”
Section: Figurementioning
confidence: 74%
See 1 more Smart Citation
“…1,2 The extragonadal YSTs are usually seen in anterior mediastinum, retroperitoneum, and suprasellar regions. [3][4][5][6] In this case, the YST was in the pineal gland, which is relatively rare. Moreover, we found that 68 Ga-FAPI PET showed a far better tumor-to-background ratio than 18 F-FDG in the intracranial YST.…”
Section: Figurementioning
confidence: 74%
“…YST is a rare germ cell tumor and typically occurs in the testis or ovary 1,2 . The extragonadal YSTs are usually seen in anterior mediastinum, retroperitoneum, and suprasellar regions 3–6 . In this case, the YST was in the pineal gland, which is relatively rare.…”
mentioning
confidence: 79%
“…[13,14] The radiological features of YST are not specific; however, familiarity with its imaging characteristics can enable preoperative diagnosis, improve surgical planning and assess effects of treatment. [15][16][17][18][19] The CT findings in two cohorts with a combined total of 31 YSTs (age range: 1-31 years) documented that lesions ranged from 5-24 cm and most were well-circumscribed with defined borders. [15,16] Intralesional calcification was rare; however, intratumoral hemorrhage, ascites and marked enhancement were common findings.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological assessment can also be employed as a surveillance method and studies have demonstrated the utility of FDG-PET/CT not only in disease detection but also in assessing response to therapy. [17][18][19] Of note, the role of novel biomarkers such as microRNAs (miR), which are short, non-proteincoding RNAs, has been investigated in disease states. [25] MicroRNAs at a few 'clusters,' miR-371-373 and miR-302-367, are overexpressed in all malignant GCTs despite anatomical location, patient age or subtype.…”
Section: Discussionmentioning
confidence: 99%
“…This patient in our case had anterior chest wall invasion. Solitary anterior mediastinum mass with increased FDG uptake should mainly arouse a suspicion of thymoma, 9,10 lymphoma, 11 carcinoid, 12 metastasis, 13 yolk sac tumor, 14 paraganglioma, 15 and follicular dendritic cell sarcoma. 16 This case hints us that extramedullary plasmacytoma should be regarded as a differential diagnosis when we encounter a solitary anterior mediastinum mass with intense FDG uptake.…”
mentioning
confidence: 99%